Recent advances in shape correspondence - Sahillioğlu, Yusuf (The Visual computer, 2020)
Important new developments have appeared since the most recent direct survey on shape correspondence published almost a decade ago. Our survey covers the period from 2011, their stopping point, to 2019, inclusive. The goal is to present the recent updates on correspondence computation between surfaces or point clouds embedded in 3D. Two tables summarizing and classifying the prominent, to our knowledge, papers of this period, and a large section devoted to their discussion lay down the foundation of our survey. The discussion is carried out in chronological order to reveal the distribution of various types of correspondence methods per year. We also explain our classification criteria along with the most basic solution examples. We finish with conclusions and future research directions.